Comparative Study of Natural Gas Adsorption Isotherms on KOH and H3PO4 Palm Kernel Shells Porous Activated Carbon - N.S. Nasri; H. Martel; I.M.H.I. Abbas; U.S. Hayatu; H.M. Zain; A. Abdulrasheed; R. Mohsin; Z.A. Majid; N.M. Rashid; Z. Sharer; A. Garba (Chemical Engineering Transactions, 2017)
Sustainable energy of Natural Gas (NG) has been an increasingly valuable and advantageous fossil fuel as it produces a cleaner combustion, and efficient consumption. Compressed Natural Gas (CNG) storage method and its utilisation has caused several problems due to high cost of installation for extensive 25.86 MPa high- pressure bulky cylinder, internal cylinder corrosion, and the possibility of releasing an explosive compressed gas. Adsorb Natural Gas (ANG) storage as a new technology, where natural gas is adsorbed in a suitable adsorbent with high porosity to increase the volume of gas stored in the vessel at lower pressure 3.45 – 5.52 MPa is a promising alternative. The energy density stored in ANG storage system is greater than the CNG vessel at the same pressure. Solid sustainable material of Palm Kernel Shell (PKS) was treated chemically to obtain adsorbent media to determine its adsorption and desorption rate performance at certain pressure. The adsorbent obtained by treatment with KOH and H3PO4 labelled as PKS-ACB and PKS-ACA. Samples were characterised by SEM, BET, TGA and FTIR. The SEM, BET, TGA and FTIR results showed promising results. The adsorption rate of the first 20 minutes was 0.038 mmol/g.min for PKS-ACA and 0.034 mmol/g.min for PKS- ACB. The desorption rate of PKS-ACA and PKS-ACB was 643 mmol/g.min and 430 mmol/g.min. There was no gas residual left in the sorbent. Findings highlighted that sustainable solid waste materials of palm kernel shell are renewable; its surface property as natural gas adsorbent storage known as ANG.